Impact of Regenerative Agriculture on Soil Biological Performance in Arabica Coffee (Coffea arabica) Cultivation - Silvia Nora; Retna Astuti Kuswardani; Surip Mawardi (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Soil health is a crucial factor in the sustainability of Arabica coffee production, particularly in addressing the challenges of land degradation caused by conventional agricultural practices. One practical approach to naturally enhance soil fertility is implementing a regenerative farming system, which focuses on increasing the diversity of soil microbes to support a healthy and productive ecosystem. This study aims to analyze and compare the diversity of soil microbes in Arabica coffee fields managed under regenerative farming systems versus those under conventional farming systems. It will identify the dominant types of microbes in each system and examine how their presence influences soil fertility. Additionally, the study will assess the impact of regenerative farming on the balance of the soil microbial ecosystem and the health of coffee plants. The methodology employed is comparative, involving soil sampling through random sampling techniques. Microbial diversity will be analyzed using culture methods, with soil microbial observation parameters including bacteria, fungi, phosphorus-solubilizing bacteria, nitrogen-fixing bacteria, respiration rates, and the carbon-to-nitrogen (C/N) ratio. Laboratory data will be analyzed using comparative statistical tests, specifically the t-test. The study aimed to identify microbial distribution patterns using PCA-Bi Plot analysis. The results indicated that the total number of bacteria, fungi, total microbes, and soil respiration rates were significantly higher in the regenerative farming system than in the conventional system. The dominant soil microbes in the regenerative farming system included nitrogen (N) fixing bacteria and decomposer fungi. A strong positive correlation (r = 0.938, p < 0.01) was observed between total microbes and soil respiration. The regenerative farming system not only increases the number of soil microbes but also enhances the biological activity of the soil. These findings underscore the potential of regenerative agriculture as a viable alternative for improving soil quality in Coffea arabica cultivation, aligning ecological benefits with agricultural productivity.